Isolated giant intrathoracic meningocele associated with vertebral corpus deformity - Turgut, Mehmet; Alhan, Cumhur; Cihangiroglu, Mutlu; Topcuoglu, Mehmet Sah (My University, 2004)
Published reports of intrathoracic meningocele with vertebral corpus defects in the absence of neurofibromatosis are very rare. We report a 9-year-old male with intrathoracic meningocele. We believe that vertebral corpus defects may play a certain role in the etiology of intrathoracic meningocele. © 2004 Elsevier B.V. All rights reserved.
Keywords: Helical CT; Intrathoracic meningocele; Neurofibromatosis